Traumatic Bilateral Mainstem Bronchial Avulsion in a Red Fox (Vulpes vulpes) - Ganz, Seth; Bartlett, Susan; Solano, Mauricio; Tseng, Florina; Pokras, Mark (Wildlife Rehabilitation Bulletin, 2006)
An adult male red fox (Vulpes vulpes) was hit by an automobile and presented in respiratory distress. Radiographs and a physical examination indicated that both bronchi had been avulsed from the lungs and euthanasia was elected. This is the first report of a bilateral bronchial avulsion, as well as the first report of large airway avulsion in a canid, as a result of blunt thoracic trauma. Tracheal avulsion is a sporadically reported sequel to blunt trauma in domestic cats. Preliminary diagnosis can be made from history, clinical signs, and radiographs. Bronchoscopy yields a definitive diagnosis. Treatment is most often surgical resection of traumatized ends of airway and anastamosis. Depending on the location and extent of injury, other surgical techniques may be considered. An index of suspicion for this injury must be maintained in any patient suffering blunt trauma, as patients with this severe injury may present with mild signs and initially respond to conservative therapy. Thoracic radiographs should be obtained promptly in all cases of suspected blunt thoracic trauma.